A study of personal financial planning practised by accountants in Kuching / Prof. Madya Dr. Hajah Fatimah Bujang, Kueh Chiok Choo and Chong Fen Nee (Universiti Teknologi MARA, Sarawak, 2005)
The purpose of this study was to gauge the practice of personal financial planning amongst accountants in Kuching. A big majority of the accountants set their financial goals based on short, medium and long-term goals and prioritized them accordingly. For each aspect of personal financial planning, the ranking of importance was as follows: retirement planning, debt management, education planning, purchase or renovation of house, emergency buffer, insurance and lastly vacation. The most popular plan for retirement planning is the Employees Provident Fund (EPF) or pension funds. It was also found that accountants in Kuching were generally very cautious and extremely risk adverse in their personal financial planning practices. Forty-three percent (43%) of the accountants' households indicated that the husbands were the primary financial advisors.